Analysis of electronic medical record acceptance among inpatient registration staff using the technology acceptance model at RS PKU Muhammadiyah Gombong - Purwati, Eli; Susena, Edy (Science Midwifery, 2025)
The adoption of Electronic Medical Records (EMR) has become an essential transformation in healthcare to enhance service efficiency and data accuracy. However, the successful implementation of EMR significantly depends on user acceptance, particularly among hospital administrative staff. This study aimed to evaluate EMR adoption at RS PKU Muhammadiyah Gombong using the Technology Acceptance Model (TAM), focusing on perceived usefulness (PU), perceived ease of use (PEOU), and behavioral intention (BI). A qualitative descriptive approach was employed through structured interviews, direct observations, and document analysis. The results showed that 75% of staff acknowledged improved efficiency and accuracy, yet 30% experienced workflow disruptions due to technical issues. Additionally, 60% found the system easy to use after training, but 25% struggled with document uploads. Major challenges included system downtime, connectivity issues, and storage limitations, with 50% of staff reporting these barriers. Training deficiencies were noted by 20% of respondents, highlighting the need for continuous learning initiatives. Management support played a vital role in implementation success, yet ongoing assistance remained necessary. Addressing technical constraints, refining training programs, and strengthening managerial engagement are crucial for optimizing EMR adoption.